Prolactin-Secreting Leiomyoma Causing Hyperprolactinaemia Unresponsive to Dopamine Agonist Therapy and Resolution following Myomectomy - Lucinda Barry; Selvan Pather; Ash Gargya; Anthony Marren (Case Reports in Endocrinology)
Prolactin-secreting leiomyomas are rare, with only eight cases reported in the literature. This case describes a 37-year-old female with hyperprolactinaemia (1846 mIU/L; 85–500 mIU/L) refractory to cabergoline causing infertility and galactorrhea. MRI pituitary was normal. The patient had a known enlarging uterine leiomyoma on serial pelvic ultrasounds (15.2 cm × 9.1 cm × 12.1 cm). The serum prolactin returned to subnormal levels two days postmyomectomy and showed recovery to normal levels in the months following surgery. Immunostaining of the leiomyoma for prolactin was negative. Despite not staining for prolactin, quick resolution of the patient’s hyperprolactinaemia after myomectomy supports the diagnosis of a prolactin-secreting fibroid. A prolactin-secreting leiomyoma should be considered in patients with hyperprolactinaemia and normal pituitary MRI which is refractory to dopamine receptor agonist therapy who also have evidence of a uterine fibroid. In patients wishing to seek fertility, myomectomy should be considered to allow for normal ovulation and possibility of future fertility.